2008
DOI: 10.1093/annonc/mdm583
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells in colorectal cancer: correlation with clinical and pathological variables

Abstract: CTCs detection by CellSearch is a highly reproducible method that correlates with stage but not with other clinical and morphological variables in patients with colorectal cancer. Colon cancer tumor cells are detectable in all stages. Further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
137
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 13 publications
12
137
2
3
Order By: Relevance
“…18). This discrepancy can be explained by the fact that Sastre et al performed blood collection after operation in TNM stage I to III colorectal cancer patients that most of them had partial or complete clearance of CTCs (18). In fact, the percentage of CK20 pCTC detection in our cohort of colorectal cancer patients at their first follow-up after operation was only 28.7% (29 of 101).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…18). This discrepancy can be explained by the fact that Sastre et al performed blood collection after operation in TNM stage I to III colorectal cancer patients that most of them had partial or complete clearance of CTCs (18). In fact, the percentage of CK20 pCTC detection in our cohort of colorectal cancer patients at their first follow-up after operation was only 28.7% (29 of 101).…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies indicated that immunomagnetic enrichment CTC detection using broad-spectrum antibody is very promising only in metastatic breast cancer (5 -7), whereas there are still very scanty reports in colorectal cancer (18,22,23). Using this refined immunomagnetic enrichment assay with standardized immunocytochemical staining and stringent assessment criteria, no CK20 pCTC was found in all blood samples from patients with breast cancer, prostate cancer, liver cancer, and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These circulating tumor cells can be detected in the blood of patients with colo-rectal cancer (CRC) before the development of metastasis (Glaves, 1983). Circulating tumor cells (CTCs) have been detected in the peripheral blood of patients with a variety of metastatic solid tumors at varying concentrations using a variety of methods, such as RT-PCR, immunocytochemistry, immunoflorescence and flow cytometry (Jonas et al, 1996: Nagrath et al, 2007: Sastre et al, 2008: Marrinucci et al, 2010. The majority of these cells will die, it has been estimated that fewer than 0.01% of CTCs will implant and form metastasis (Fidler, 1973), and most CTCs are cleared from the circulation within 24 hours (Fidler, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Progress in the detection of CTC was achieved by immunohistochemistry testing [6] and, more recently, by highly sensitive PCR techniques [7][8][9]. In patients with colorectal cancer, the presence of CTC in peripheral blood was repeatedly confirmed and their detection ranged from 20% for localized disease and 60% in advanced CRC [10][11][12][13][14][15][16][17][18]. The clinical relevance of CTC as an independent prognostic factor was documented for cases in patients with positive CTC at diagnosis who had poorer prognosis than patients with negative CTC [10,[12][13][14][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%